Karakterisasi Sinbiotik Ekstrak Tepung Rebung Bambu Tabah (Gigantochloa Nigociliata Buse-Kurz) Dengan Lactobacillus Sp. Ar6152 - Putu Agus Nadiarta; Nyoman Semadi Antara; Ida Bagus Wayan Gunam (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2022)
Tabah bamboo shoots (Gigantochloa nigrociliata Buse-Kurz) flour can be used as a prebiotic because it has oligosaccharides such as stakiosa and rafinosa.Tabah bamboo shoots flour has ability to produce short-chain fatty acids derived from the fermentation of digestive tract lactic acid bacteria (LAB) and Lacobacillus rhamnosus. In tabah bamboo shoots pickle there are also LAB that are able to survive at low pH and bile salts, one of the potencial bacteria is Lactobacillus sp, AR6152. In this study, experiments were conducted synbiotic characteristics of stoic bamboo bamboo shoots with Lactobacillus sp AR6152 with 3 formulas between prebiotics and probiotics using a ratio of 1:2 (Sinbiotic A), 1:1 (Sinbiotic B) and 2:1 (Sinbiotic C) and additional ingredients as a coating 1 g of casein and 20 g of maltodextrin for 100 mL of synbiotic solution. The synbiotic solution is dried with freeze dry until it becomes a powder. The purpose of this study was to find out the viability of Lactobacillus sp AR6152 with an observation time of 0 weeks, 1 weeks, 2 weeks 3 weeks and 4 weeks, and the microcapsule morphology of product. The results showed that the resulting microcapsules have an irregular shape because using freeze-drying method as drying technic and smooth microcapsules surfaces and without holes due to the use of casein and maltodextrin as a coating material affects the viability of Lactobacillus sp. AR6152 is classified as stable in log 1011. The viabillity of Lactobacillus sp. AR 6152 decrease after 2 weeks of storage. In the Synbiotic B decreases less in week 0 and 2 compared to synbiotic Synbiotic A and Synbiotic B. In Synbiotic B in week 0 as much as (3.5 ± 0.03) ×? 10?^11 CFU/g and down to (3.2 ± 0.02) ×? 10?^11 CFU/g and (1.9 ± 0.02) × ? 10?^11 CFU/g in week 2 and 4.